Peningkatan Sikap Peduli Lingkungan Siswa melalui Metode Pemberian Tugas dalam Pembelajaran IPS di SMP Negeri 1 Anggrek - Olis Ahbabuna; Radia Hafid; Rierind Koniyo; Frahmawati Bumulo; Sudirman Sudirman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to find out the increase in students' environmental care attitudes and what factors affect the success of the task method in improving students' environmental care attitudes. This type of research uses a qualitative approach, with. Data collection in this study used interview and documentation guidesheets. The research subjects consisted of 2 people as key informants and 4 people as supporting informants. Each of them is the principal, social studies teacher and students of SMPN 1 Anggrek. The results of this research based on the results of interviews are an increase in the attitude of caring for the environment in the method of assigning tasks. The assignment method is a method that presents materials when the teacher gives certain tasks that aim to make students carry out learning activities. The method of assigning assignments is not the only method in improving students' environmental care attitudes, so their success is influenced by several factors including; student interests, school policies on the environment and the role of teachers. In conclusion, the role factor of teachers is the most needed: where teachers have an important role in shaping the character of caring for the environment. The example of the teacher is very influential, when the teacher shows environmentally friendly behavior, students tend to follow the example. Even without assigning assignments, teachers must also be an example of how to care for the environment, so that it will build awareness for students to always care about their environment In addition, as a teacher, they must have creativity, especially in using the method of assigning assignments.